PENGARUH MODEL PEMBELAJARAN PROBLEM SOLVING BERBANTUAN MEDIA MKET TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA TAHUN AJARAN 2019/2020 - Naema Kamaleng; Fransina Th Nomleni (Indigenous Biologi : Jurnal Pendidikan dan Sains Biologi, 2020)
The problems found by students who are less active in the learning process carried out in class are seen from the students who still look passive in asking and answering questions raised by the teacher and raising ideas or ideas, students' ability to learn the concepts that make it difficult for students to explain the material with words alone. The purpose of this study was to determine the effect of the model of problem solving learning assisted by mockup media on students' critical thinking skills. This type of research used is experimental research (experimental). The design of this research is True experimental design in the form of posstest-only control design. The research procedure is the preparation phase and the implementation stage. Data collection techniques using tests were analyzed using t tests. The results of this study indicate that there is an influence on students' critical thinking skills after using the model of problem solving learning assisted by the media model, this is shown from the use of the problem solving learning model where students can solve problems and find solutions, with the media model as a concrete media showing a picture of pollution water clearly so that attracts the attention of students as for the advantages of media models that can represent as contained in nature, students can experience learning directly, direct observation can be observed by students by observing objects directly or imitations, and can show the flow of a process clearly . This can be seen from the average value obtained from the 84.05 experimental class while in the control class 63, 20 and included in the very good category. Thus it can be concluded that learning using a model of problem solving learning assisted by mockup media can improve critical thinking skills.